Writing the decline : on the struggle for South Africa's democrac y - Pithouse, Richard, 1970- (Auckland Park : Jacana Media (Pty) Ltd, 2016)
"There is a growing sense that the promise of democracy in South Afr ica has not been adequately redeemed. This book tracks the steady decay of that promise in recent years. Written from an understanding that de mocracy should be for everyone, rather than merely a contest between el ites, it explores the growing authoritarianism of the state, the deepen ing social crisis, and the avenues of hope and possibility. In a moment when old certainties are breaking down, and new ideas and social force s are taking the stage, this book offers a compelling invitation to tak e democracy seriously."--Back cover.
Introduction -- The May 2008 pogroms -- A state of emergency for the poor -- Burning message to the state in the fire of poor's rebellion - - The devestation of Haiti -- Eskom -- Universities for bread and roses -- The casual bulldozing of a Shembe temple in Durban -- Revolution co mes like a thief in the night -- Only protected on paper -- The murder of Andries Tatane -- A path through the embers -- The return of the Eng lish riot -- On the Wall Street occupation -- Locusts on the horizon -- From Ramle Prison to the world -- No Zunami on the streets -- The thir d force -- Climbing Jacob's ladder -- The riotous underbelly of the new normal -- From Delhi to Bredasdorp -- The strongest of the strange (fo r Bradley Manning) -- A hundred years of the 1913 Land Act -- Promise a nd peril at the turn of the tide -- There will be blood -- The murder o f Nqobile Nzuza -- Nelson Mandela: the crossing -- Four bodies in three weeks -- On the crimson carpet -- Homophobia on the march -- Marikana, resolve and resilience -- Marikana, Gaza, Ferguson: 'You should think of them always as armed' -- After the end of our innocence -- Riot poli ce in Parliament -- On not reducing racism to apartheid -- Land, dignit y and democracy -- Rhodes must fall -- Reason after liberalism -- Praxi s and social mobilisation -- Charleston (It's not over) -- They 'die th ere, it matters not where, nor how' -- A moment of possibility for univ ersities -- As real as the smell of rain on dry earth.
Keywords: Democracy -- South Africa; South Africa -- Politics and government